La burocracia mexicana como actor: construyendo las bases para su análisis empírico - David Arellano Gault (Nuevo mundo - Mundos Nuevos, 2009)
Empirically speaking, the bureaucratic actor has been scarcely studied in Mexico. The history of one-party domination made this actor, at the federal level, to be considered as an appendix or machine at the service of the political regime. The theory of camarillas has been predominant ever since. However, the camarilla is a weak argument nowadays. Public servants belonging to a camarilla are not the majority, as the implementation of civil service in Mexico is shown. It is needed to strengthen the empirical study of this important actor in order to understand (1) the political role this actor is building today and (2) the organizational behavior bases which are structural part of the administrative apparatus in a country like Mexico.